Effectiveness of a Structured Self-Management Intervention to Improve Quality of Life in Individuals With Chronic Obstructive Pulmonary Disease (AMPOC Study) - Maite López Luque; Marta Chuecos Molina; Guadalupe Ortega Cuelva; M. Jesús Vázquez López; Francisco Orfila Pernas; Nina Granel Giménez; Esther Ruiz Rodríguez; M. Ángeles Santos Santos; Adrià Almazor Sirvent; Antonio Vallejo Domingo; Toni López Ruiz; Purificación Jordana Ferrando (Open Respiratory Archives)
Introduction: This study aimed to compare the effectiveness of a structured self-management program in patients with moderate–severe COPD followed up for 12 months, in improving quality of life, dyspnea, inhaler adherence, anxiety, and depression, compared to standard practice. Material and methods: This was a multicenter randomized clinical trial involving 115 patients, 59 in the intervention group and 56 in the control group. Participants from 16 primary care centers in Barcelona, Spain, were allocated consecutively and in a blinded manner to the intervention and control groups in stages. Professionals received training in behavioral change techniques. The intervention consisted of four 20-min sessions conducted at 14-day intervals, covering topics such as COPD knowledge, smoking, inhaler use, physical activity, nutrition, breathing, exacerbations, vaccinations, work and environmental conditions, leisure, sexuality, daily activities, anxiety, and depression. Results: A total of 102 patients completed the study, 50 in the intervention group and 52 in the control group. Differences between the intervention and control groups in quality of life, dyspnea, inhaler adherence, smoking, anxiety, and depression were not significant. Conclusion: In patients with moderate–severe COPD, a structured self-management intervention in primary care is not more effective than standard care in improving quality of life, dyspnea, inhaler adherence, anxiety, and depression. Resumen: Introducción: El presente estudio se realizó con el objetivo de comparar la efectividad de un programa estructurado de autocuidado en pacientes con EPOC moderado-grave con seguimiento a los 12 meses centrado en la mejora de la calidad de vida, disnea, adherencia a los inhaladores, ansiedad y depresión con respecto a la práctica habitual. Material y métodos: Ensayo clínico aleatorio multicéntrico. Participaron 115 pacientes, 59 en el grupo intervención y 56 en el grupo control a los que se les hizo seguimiento a los 12 meses. La muestra fue obtenida de 16 Centros de Atención Primaria en Barcelona, España, en la que se realizó la asignación de los centros al grupo intervención y al grupo control, por etapas, consecutivamente y de forma ciega. Se realizó una formación a los profesionales asociados al estudio en técnicas de entrevista motivacional, motivación para el cambio y retroalimentación positiva. La intervención a los pacientes consistió en 4 sesiones de 20 minutos separadas 14 días, sobre conocimientos de EPOC, tabaquismo, uso de inhaladores, actividad física, nutrición, respiración, exacerbaciones, vacunaciones, entorno laboral y ambiental, ocio, sexualidad, actividades cotidianas, ansiedad y depresión. Resultados: Finalizaron el estudio 102 pacientes, 50 en el grupo intervención y 52 en el grupo control. Las diferencias entre el grupo intervención y el grupo control en la calidad de vida, disnea, adherencia a los inhaladores, tabaquismo, ansiedad y depresión fueron no significativas. Conclusión: En pacientes con EPOC moderado-grave, una intervención estructurada en autocuidado en atención primaria con seguimiento a los 12 meses no es más efectiva que la intervención habitual en la mejora de la calidad de vida, disnea, adherencia a los inhaladores, ansiedad y depresión.